PENGARUH EARNINGD PER SHARE (EPS), DEVIDEND PER SHARE (DPS), PRICE EARNINGS RATIO (PER) DALAM HARGA SAHAM (STUDY KASUS PADA PERUSAHAAN INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020) - Faruq Hidayatullah; Lailatus Sa’adah; Kartika Wulandari (Jurnal Inovasi Penelitian, 2022)
This study aims to analyze the effect of Earnings Per Share (EPS), Dividend Per Share (DPS), Price Earnings Ratio (PER) on stock prices in infrastructure companies listed on the Indonesia Stock Exchange 2016-2020. This type of quantitative research uses panel data with classical assumption analysis techniques multicollinearity test, normality test, heteroscedasticity test, multiple linear test, T test, F test and coefficient of determination. The results of the study are Earnings Per Share (EPS) Dividend Per Share (DPS), Price Earnings Ratio (PER) has an influence on stock prices with T test results with a significance value of Earning Per Share variable significant probability value of 0.00 which is smaller 0,05. Price Earning Ratio significant probability value of 0.00 which is smaller than 0.05. and Dividends per Share a significant probability value of 0.020 which is smaller than 0.05. And for the F (simultaneous) test, the significance probability value is 0.000 which is smaller than 0.05.